Meningkatkan Kemampuan Komunikasi Horizontal Melalui Media Virtual Pada Masa Pandemi Covid-19 Guru Mas Nurul Hadina Patumbak II - Ikwan Ikwan; Maringan Sianturi; Edward Robinson Siagian (Jurnal ABDIMAS Budi Darma, 2022)
The importance of horizontal communication skills is something that MAS teachers Nurul Hadina Patumbak II must possess. This is because horizontal communication ability is one of the competencies of teachers that can be used as a medium in the process of interaction with the community as an effort to provide understanding to the community about the importance of the role of Madrasah Aliyah Nurul Hadina Patumabak II in preparing students' resilience in the face of changing times. and carry out Islamic da'wah in seeking to develop the independence of students in learning, working, and entrepreneurship. Lately, very few teachers are able to implement horizontal communication skills, not only personally but also in teamwork, this greatly affects the personality of the teachers in socializing both on campus and in the midst of society. Ideally teachers should be able to implement horizontal communication skills both theoretically and practically, for that it is necessary to have a comprehensive and actual understanding, one of the principles rarely possessed by good teachers is the lack of integrity in socializing in the campus environment. To find the solution above, a training to improve horizontal communication skills was held both in the form of practical and theoretical understanding, which was held through zoommeeting, this training will be held in February 2022. The implementation of service activities takes place on Thursday from 08.15 to 10.30 WIB, with attended by 37 participants. The activity is in the form of delivering material in the form of a Webinar. Where this service activity has relevance to the developing situation in the field. Based on the survey results before the training, students who have horizontal communication skills during the pandemic are still low. So with this training, it is hoped that students in the campus environment can have good horizontal communication skills